Changing the hierarchical placement of soil moisture regimes in Soil Taxonomy. Issue 3 (18th April 2021) - Stolt, Mark H.; O'Geen, Anthony T.; Beaudette, Dylan E.; Drohan, Patrick J.; Galbraith, John M.; Lindbo, David L.; Monger, H. Curtis; Needelman, Brian A.; Ransom, Michel D.; Rabenhorst, Martin C.; Shaw, Joey N.
Abstract: Soil moisture and temperature are incorporated into Soil Taxonomy through the broad classes of moisture and temperature regimes. Although both are important variables in soil formation and land use, soil temperature regime (STR) is typically applied at the family level, whereas soil moisture regime (SMR) is applied at the suborder level. In this paper, we are questioning whether moving SMR to the family level will create a classification system that is more efficient and provide more information to the user at higher categories. The pros and cons of moving ustic, xeric, and udic SMRs from suborder to family category are discussed. To explore this potential change, we used Shannon diversity (Δ H ) as an index of the information gain moving from order to suborder when classifying a soil. The analysis indicated a relatively small Δ H for most of the country considering current suborder classes. The proposed group of suborders, characterized by diagnostic horizons instead of SMR, conveyed a considerably larger Δ H supporting a substantial gain in information if the change was incorporated into Soil Taxonomy. The proposed change also has the potential to reduce the number of subgroup taxa by nearly 50%, without losing any of the current information within each taxa. Counterarguments for the change are that SMRs have soil genesis connotations and provide a way to group similar soils on broad‐scale maps. A change in the hierarchy of SMRs within Soil Taxonomy could deemphasize the relevance of soil moisture to soil genesis, morphology, and ecology. Core Ideas: Many aspects of Soil Taxonomy need changing for a more efficient system. Soil classification could be more efficient if soil moisture regime (SMR) was at the family level. SMR at the suborder level provides insight into soil genesis. SMR at the suborder level allows for creation of broad‐scale maps. Soil use decisions may be better served with diagnostic properties at the suborder level.